Prehypertension and socioeconomic status: A cross-sectional study in Chongqing, China - Rui Zhang; Runze Deng; Pengyu Shen; Mingyue Fan; Bing Leng; Yujia Zhou; Yadeng Cui; Ge Li (Clinical and Experimental Hypertension, 2017)
Background: A large amount of research is available on the relationship between socioeconomic status (SES) and hypertension. However, the relationship between SES and prehypertension remains complex and unclear. Prehypertension is defined as a systolic blood pressure (SBP) between 120 and 139 mmHg or diastolic blood pressure (DBP) 80 and 89 mmHg. This paper focuses on the impact of SES on the prevalence of prehypertension and provides suggestions for the prevention and control measures of prehypertension and health resource allocation. Method: Using multistage random sampling, 11,773 subjects were selected. Subjects aged above 15 years old and subjects who had been living in the eight selected districts for more than 6 months were analyzed using a multivariable logistical model. Results: The prevalence of prehypertension at the present time reaches 55.17%, with it being higher among men than that among women (63.15% vs. 47.19%, p < 0.05). After adjustment for other factors such as age and gender, a logistic regression showed that a higher education level and a history of marital status were significantly associated with prehypertension. Conclusions: People of different SES indicate different working and living conditions. They also face different risk factors for prehypertension. Lower education and a history of marital status were associated with a higher risk of prehypertension among residents in Chongqing, China